Pengembangan Perangkat Lunak Smart Trash Terintegrasi IoT dengan Sterilisasi UV-C dan Pengujian Blackbox Berbasis Scrum - Dian Resti Juliani; Irman Hariman (Journal Data Science, Technology, Informatics and Security, 2024)
Serious challenges in waste management in Indonesia have had a significant impact on health and the environment. The excessive accumulation of waste has led to new issues, including a decline in environmental quality and the spread of diseases. This study employs a qualitative approach to address this problem. The Scrum methodology is employed in software development, with an emphasis on blackbox testing and Boundary Value Analysis (BVA). Research findings reveal issues in waste management, including excessive accumulation and bacterial growth in waste disposal sites. A proposed solution is presented through an IoT and Android-based "Smart Trash" system, incorporating weight and height sensors for waste, UV-C Lamp technology, and notification delivery to Android devices. A prototype of this tool is tested to optimize waste monitoring and management. The research findings conclude that this smart waste disposal system facilitates monitoring and notifications for sanitation workers, while aiding in minimizing bacterial growth in waste. With this system in place, sanitation workers can manage waste transportation more efficiently. However, this tool holds potential for further development, such as bacterial detection in waste.